Pengaruh Layanan Informasi Karir Terhadap Perencanaan Karir Siswa SMP Negeri 12 Palu Kelas IX - Anastasya, Anita; Nurwahyuni, Nurwahyuni; Puswiartika, Dhevy; Fitriano, Dian (Jurnal Ilmiah Dikdaya, 2024)
This study aims to determine the effect of career information services on students' career planning. The research method uses quantitative with a quasi-experimental type of research, data collection techniques to identify students' understanding of career planning are questionnaire instruments. The subjects in this study were all students of class IX A totaling 21 and Class IX B totaling 22 so that the total number of subjects was 43 students, the sample used was Nonrandom assignment. Data analysis used descriptive analysis and inferential analysis using the Kolmogorov-Smirnov t test. The results of the descriptive analysis showed that of all students of class IX SMP Negeri 12 Palu, namely 43 students, they were stated to have increased their understanding of career planning after being given career information services. This can be seen from the total research subjects, namely 43 students. Where previously there were 28 students who had a low career understanding from the less to good classification. Then for the entire subject as many as 43 students experienced an increase, namely two of them were classified as very good and 41 of them were classified as good. The results of the inferential analysis showed that career information services had a significant effect on the career planning of class IX students of SMP Negeri 12 Palu. This can be seen from the research subjects after being given career information services based on the data obtained showing an increase from the low level of student career planning with a significant average increase. From the results of this study, it can be proven that career information services have an effect on improving student career planning.